AN ANALYSIS OF READING MATERIALS QUALITY OF ENGLISH TEXTBOOK “BAHASA INGGRIS” FOR SMK NEGERI 2 PALANGKA RAYA - Riezki Faradiena; Hesty Widiastuty; Zaitun Qamariah (PROJECT (Professional Journal of English Education), 2022)
The aim of the study was to discuss the quality of reading materials in a textbook “Bahasa Inggris” for secondary school which was used in SMK 2 Palangka Raya based on Badan Standar Nasional Pendidikan (BSNP) criteria in term of aspect of content, language, and presentation. The research utilized a descriptive qualitative approach. The design of study conducted content analysis. The instruments were observation checklist based on BSNP criteria. Secondary instrument was documentation to support primary instrument. The researcher found that dominantly of the aspects fulfilled. However, a point of six in aspect of content was not found in the English text book. Moreover, two of seven points in presentation aspects did not exist within it. Keywords:  Textbook Analysis, English Textbook, Reading Material, Badan Standar Nasional Pendidikan Criteria